PENGARUH INSENTIF, KOMPENSASI DAN REWARD TERHADAP KINERJA KARYAWAN PT. BRI (PERSERO).TBK KANTOR CABANG BENGKULU - Fauzan Fauzan (Universitas Prof. Dr. Hazairin SH, 2018)
This study aims to determine how much influence the incentives, compensation and rewards on the performance of employees of PT. BRI Persero Tbk Bengkulu Branch Office. Data analysis method uses Multiple Linear Regression, with Incentives as Free Variable (X1), Compensation as Free Variable (X2), Reward as Free Variable (X3) and Employee Performance as dependent variable (Y). that there is a positive influence between the four variables. The value of the correlation coefficient (r) is 0.760 and the coefficient of determination Adjusted R square of 0.549 shows the influence of incentives, compensation, and rewards on Employee Performance is very strong.